Inclusive Workforce Education: Towards a Feminist Pedagogy for Vocational Programs - Sarah Ray; Ovidio Galvan; Jill Zarestky (Adult Education Research Conference, 2017)
Vocational education provides economic opportunity but often excludes women. The present literature review lays the foundation to develop relevant feminist perspectives and guide the inclusion efforts of community colleges.
Keywords: feminist pedagogy; vocational education; workforce education